Nitrogen and phosphorus absorption capability in environmental culture by Taiwan gravestone Anadonta woodiana Lea - Yuni Puji Hastuti; Kukuh Nirmala; Tyas Setioaji (Jurnal Akuakultur Indonesia)
Nitrogen and phosphorus in a water culture are derived from the metabolism of the farmed organism, feed residue and microbial activity in the water. One way of controlling water quality due to waste in the form of nitrogen and phosphorus from aquaculture is to utilize filter feeder organisms of Anadonta woodiana Lea. This study aimed to analysis the effectiveness of the absorption of nitrogen and phosphorus in waters by A. woodiana as filter feeder. A total of 0 (control), five, ten, and 15 gravestone were putted into a tank of 35 L of water derived from Cirata reservoir. Each treatment was given three times repetition. Measurement of total nitrogen and phosphorus in gravestones were performed at baseline and end of treatment. In addition, measurement of total nitrogen and phosphorus in the water tank was measured every ten days. Another measurement is the length and weight of gravestone. Direct observations made on gravestones barnacle survival, pH, dissolved oxygen, temperature, and turbidity every day. Aeration was provided in each aquarium. Based on the results obtained, the survival of gravestone in the density of five gravestones was 93.33%, in ten gravestones density was 90%, while in 15 gravestones was 95%. The percentage reduction in total nitrogen in the water at the end of treatment was 57% for the five gravestones density, and for ten gravestones was 88.2%. The decrease of total phosphorus in water in ten gravestones density was 37.4%, whereas the increase in density of 15 gravestones and total phosphorus water percentage was 26.9%. On the density of ten gravestones, the body weight decreased until to 3.3%, while in the density of 15 gravestones decreased until to 2.5% on day 30. Results of water quality analysis showed that the DO values decreased from baseline to end of treatment (from 5.08 to 4.86 mg/L), the average water temperature from 26.5 to 27.4 °C, pH values 7‒8, and highest turbidity values was obtained in the density of five gravestone. Decrease in the percentage of total nitrogen in the water suggested nitrogen and phosphorus have been absorbted for barnacle growth.